The Influence of Entrepreneurial Education on Entrepreneurial Intention within Indonesian Student - Mubarok, Teten Mohamas Sapril; Martiara, Dewina; Hamdani, Nizar Alam; Permana, Intan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The objective of this paper is to examine the effect of entrepreneurial education on entrepreneurial intention. Moreover, the paper examines how dimensions correlate with entrepreneurial intention. It is concluded that entrepreneurial education has a significant effect on entrepreneurial intention. This research has benefited that entrepreneurial education to carry out entrepreneurial intention. In addition, the study also finds a significant effect entrepreneurial education on entrepreneurial intention. The analysis of the paper is based on survey responses from 31 Indonesian student at high education